Service Delivery Indicators : Kenya - Martin, Gayle H.; Pimhidzai, Obert (World Bank, Washington, DC, 2014)
Without consistent and accurate information on the quality of services, it is difficult for citizens or politicians (the principal) to assess how service providers (the agent) are performing and to take corrective action. The service delivery indicators (SDI) provide a set of metrics to benchmark the performance of schools and health clinics in Africa. The indicators can be used to track progress within and across countries over time, and aim to enhance active monitoring of service delivery to increase public accountability and good governance. Ultimately, the goal of this effort is to help policymakers, citizens, service providers, donors, and other stakeholders enhance the quality of services and improve development outcomes. This report presents the findings from the implementation of the first SDI survey in Kenya. The production of health services requires three dimensions of service delivery: (i) the availability of key inputs such as drugs, equipment and infrastructure; (ii) providers who are skilled; and (iii) providers who exert the necessary effort in applying knowledge and skills. The SDI surveys allow for the assessment of how these elements come together to produce quality health services in the same place at the same time. This paper is structured as follows: section one gives introduction. Section two outlines the analytical underpinnings of the indicators and how they are categorized. Section three presents the methodology of the Kenya SDI education and health surveys. The results are presented and analyzed in section four and section five. The report concludes with a summary of the overall findings and some implications for Kenya.